ChatGPT in early childhood STEM education: Can it be an innovative tool to overcome challenges? - Ugras, Hilal; Ugras, Mustafa (Springer, 2025)
The aim of this study is to determine the effectiveness of using ChatGPT, an artificial intelligence-supported tool, to overcome the challenges in the implementation of early childhood STEM education based on teachers' views. In the study, a case study, which is a qualitative research method, was used. The participants of the study consisted of 43 early childhood teachers specialized in the field of STEM education who were determined by purposeful sampling method. Within the scope of the study, a training program was developed for teachers to integrate ChatGPT into early childhood STEM education and teachers voluntarily participated in this program. During the training process, the researchers collected data through observation reports and semi-structured interviews conducted after the training. The collected data were subjected to content analysis using MAXQDA software, and themes, categories and codes were identified. The findings revealed the teachers' views that the use of ChatGPT in early childhood STEM education would be beneficial. It was determined that ChatGPT would provide advantages such as guidance, effective use of existing materials, the opportunity to design student-specific activities, and the potential to complete teachers' missing knowledge. However, teachers also think that ChatGPT may cause negative situations such as technological addiction, regression in social skills, damage to the teacher-student relationship and misinformation. In conclusion, ChatGPT can benefit students' education.
Keywords: Early childhood STEM education; ChatGPT; Artificial intelligence; Challenges in STEM education